The Fear of Missing Out - Lim, Wesley; Phau, Yong Mi; Cheah, Isaac; Teah, Hui Min (Global Alliance of Marketing & Management Associations, 2017)
This paper seeks to conceptualize the phenomenon known as the “Fear of Missing Out” by developing and validating a measurement scale – “Fear of Missing Out” (FOMOSCALE) to be used in a marketing context. It will also further explore various antecedents that may impact on FOMO. The study suggests an alternative approach towards the conceptualization of FOMO by defining it as a personality trait as opposed to an outcome of a behavior.